U.S. AND EUROPEAN PRACTICES IN MANAGING CREDIT RISK IN COMMERCIAL BANKS AND THE PROSPECTS FOR THEIR APPLICATION IN UZBEKISTAN - Norova , Nozima (Journal of Fundamental Studies, 2026)
This study provides a systematic analysis of advanced practices in credit risk management developed within commercial banking systems in the United States and Europe. The research comprehensively examines mechanisms for assessing and controlling credit risk, including credit policy and the risk appetite framework, the application of internal rating and scoring models, stress-testing practices, methodologies for estimating expected credit losses (ECL), and approaches to managing non-performing loans. In addition, the study analyzes the institutional foundations of stress testing and capital planning mechanisms in the U.S. banking system, as well as their integration into the macroprudential supervisory framework. In the European banking context, particular attention is given to the requirements for measuring expected credit losses under IFRS 9, prudential standards applied to internal rating models, and the validation processes conducted by supervisory authorities.